Kelayakan Mobile Learning Media pada Materi Fisika Inti dan Radioaktivitas - Dandan Luhur Saraswati (UIN Sunan Gunung Djati Bandung, 2019)
On the subject of core physics and radioactivity audio-visual explanations are needed. Therefore, learning media are needed that can display audio visual in order to help students in learning independently. One of the learning media for mobile learning that can be used is an android application. The purpose of this study was to determine the feasibility of a physics learning media based on mobile learning on core physics and radioactivity material developed. The stages of product development are carried out based on six stages, namely concept, design, material collecting, assembly, testing, and distribution. The data collection technique used is the product evaluation questionnaire. Product evaluation questionnaires are used to assess product development by material experts and media experts. The validation test results obtained by material experts score 83.27% and media experts obtained a score of 88.15%. Based on the results of the feasibility test, physics learning media based on Android applications on the subject of core physics and radioactivity have an average value of 85.71% with a very good interpretation. So that this product can be field tested for users to get a product that is suitable for use as an alternative learning media in the classroom